A quality improvement project to improve the accuracy in reporting hospital acquired infections in post cesarean section patients in a district hospital in Rwanda. Issue 4 (12th September 2016) - Nyiratuza, Adeline; Wong, Rex; Adomako, Eva; Habagusenga, Jean D'Amour; Nadew, Kidest; Hitayezu, Florien; Nirere, Fabienne; Murekezi, Emmanuel; Nzayirambaho, Manassé
Abstract : Purpose: Hospitals are responsible for protecting the well-being of their patients and staff. To do so, accurate information is needed for the hospital to make appropriate decisions and allocate resources efficiently. This study aims to describe the implementation process of a surveillance system to reduce hospital-acquired infection (HAI) reporting errors in the maternity unit of a district hospital in Rwanda. Design/methodology/approach: The team adapted an evidence-based tool to identify and report HAI, provided training to staff and distributed reporting responsibilities equally between the maternity staff to improve accuracy in HAI reporting. Findings: The intervention successfully reduced the reporting discrepancy of HAI from 6.5 to 1.9 per cent: p < 0.05. Practical implications: This case study described the implementation process of a surveillance system using strategic problem solving to reduce HAI reporting errors. The results can inform hospitals in similar settings of the steps to follow to implement a cost-neutral HAI surveillance system to reduce reporting errors. The accurate data will enable the hospital to take corrective measures to address HAI in the future. Originality/value: The results will inform hospitals in similar settings of steps to follow to implement a cost-neutral HAI surveillance system using the SPS approach to reduce reporting errors.